Evaluating well-being and psychosocial risks in academia: Is management the “forgotten phase”? - Bruno, Andreina; Dell’Aversana, Giuseppina; Gilardi, Silvia (Frontiers in Psychology, 2024)
In recent years, there has been a noticeable increase in attention towards promoting well-being within academic settings. In the specific context of academia, a critical issue is understanding whether the current practices for assessing and managing well-being can bridge the implementation gap and increase opportunities for creating healthy academic conditions. The paper explores the practices adopted for assessing and managing work-related stress (WRS) risks in Italian academia by referring to data from a group of Italian universities of the QoL@Work network (Quality of Life at Work in academia). The aim is to improve understanding of the factors that influence the realization of a WRS risk assessment-management pathway and how they may facilitate or hinder the transition from assessment to the implementation of interventions in the academic context. The results suggest that the assessment-management pathway should prioritize the creation of organizational scaffolding to support participatory processes in order to prevent the data collected from failing to stimulate organizational change in working conditions.